Body Mass Index With Dysmenorrhoea In Adolescents Girl - Vidia Effendy, Henny; Mustika Sari, Surya (Universitas Islam Lamongan, 2024)
Dysmenorrhoea is one of the most common menstrual disorders in adolescent girl and has quite serious effects because it can cause disruption of daily activities. One factor that causes dysmenorrhoea is due to an abnormal Body Mass Index. This study aims to determine the relationship of Body Mass Index with dysmenorrhoea in adolescent girl. This research was at SMPN 1 Mojoanyar Mojokerto. The population in this study were all adolescent girls of class X majoring in OTKP at SMPN 1 Mojoanyar Mojokerto who met the study criteria amounted to 51 people. The sample in this study were some of the adolescent girls of class X majoring in OTKP at SMPN 1 Mojoanyar Mojokerto who met the research criteria amounted to 45 people. The sampling technique used is probability sampling with sampling techniques using simple random sampling. This type of research is a non-experimental correlational research with cross sectional method. The instruments used in data collection were weight scales, height measurements, observation sheets, and NRS pain measurement scales. The data analysis technique used is the Spearman correlation test using the SPSS program. The results of this study indicate that the respondents who experience severe dysmenorrhoea most are those who have a heavy fat BMI that is as many as 7 respondents (87.5%) with statistical test results showing sig. 0.002 < α (0.05) which means that there is a significant relationship between Body Mass Index (BMI) and dysmenorrhoea in adolescent girl in SMPN 1 Mojoanyar Mojokerto. Looking at the results of this study, it is necessary to control the Body Mass Index (BMI) in order to minimize the frequency of dysmenorrhoea experienced by adolescent girl.